2006
DOI: 10.4142/jvs.2006.7.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of mature SAG1 gene of an IndonesianToxoplasma gondiiand comparison with other strains

Abstract: Toxoplasma gondii is a persistent protozoan parasite capable of infecting almost any warm-blooded vertebrates. SAG1 (p30) is the prototypic member of a superfamily of surface antigens called SRS (SAG1-related sequence). It constitutes the most abundant and predominant antigen. In this paper the primary structure of mature SAG1 gene of an Indonesian T. gondii isolate is described and sequence comparison is made with published sequence data of 7 other strains or isolates. Sequence comparison indicated that SAG1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A previous study by Hartati et al (2006) on the SAG1 gene from goat isolate in Indonesia reported a genuine T. gondii RH type I strain, which was similar to the result by Dubey et al (2008) on SAG1 and SAG2 locus from chicken isolates. However, later analysis on 10 genetic markers showed that the chicken isolate was a nonclonal genotype ToxoDB#89, which was only found in Indonesia (Chaichan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…A previous study by Hartati et al (2006) on the SAG1 gene from goat isolate in Indonesia reported a genuine T. gondii RH type I strain, which was similar to the result by Dubey et al (2008) on SAG1 and SAG2 locus from chicken isolates. However, later analysis on 10 genetic markers showed that the chicken isolate was a nonclonal genotype ToxoDB#89, which was only found in Indonesia (Chaichan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…Among the several cloned genes encoding T. gondii antigens, the surface antigen 1 (SAG1) (also named P30) has proved to be a good candidate for serodiagnosis of toxoplasmosis (10,18). In fact, it is a highly conserved antigen in most T. gondii strains examined (19,20,21), is extremely immunogenic, and is recognized during the acute and chronic phases of toxoplasmosis (22,23,24).…”
mentioning
confidence: 99%
“…The SAG1 is a good candidate for serodiagnosis of toxoplasmosis using cloned genes of T. gondii [ 45 , 46 ]. It is an immunodominant antigen highly conserved in nature and used to identify different strains of T. gondii [ 47 , 48 ]. Native SAG1 protein has six intramolecular cysteine bridges, making it an immunodominant antigen with immunologically conserved epitopes.…”
Section: Introductionmentioning
confidence: 99%